EVALUASI & OPTIMALISASI TEKNIK OPERASIONAL PENGELOLAAN SAMPAH PADA KECAMATAN PURBALINGGA KABUPATEN PURBALINGGA - Widoretno Ayuningtyas (Jurnal Teknik Lingkungan, 2012)
Along with the increasing number of urban population and urbanization, it will grow a lot of waste generated as well. According to the Department of Hygiene and the city, the rate of domestic waste generation in the Purbalingga is 2,734 L / person / day, so that waste generation in the Purbalingga each day is 132,40 m3/day. But the ministry is still 84%. To reduce the amount of waste generated in the Purbalingga district has made ​​the electoral garbage in their respective homes. Given the role of such a society, the waste produced by the settlement will be slightly reduced, where the waste could still be recycled back can still be useful. Based on the need to evaluate the condition of the existing waste management and to the development of waste management systems in the Purbalingga.